Aplicação da técnica polarização potenciodinâmica linear em análises de corrosão de revestimentos de cromo duro em meio aquoso contendo cloreto - Rolim, David Matheus de Oliveira (Universidade Federal Rural do Semi-Árido, 2021)
Electroplating is the process of coating parts with metallic material through the use of electrolysis. Among the metals used as coatings, chrome stands out. In industry it can be used for decorative or technical coatings, as in the case of hard chrome, giving certain properties to the surfaces of parts, such as hardness and wear resistance, and to protect them from the effects of corrosion. However, the electrolytes used to obtain conventional hard chrome coatings have high toxicity due to the presence of CrO3 ion, which is known to be carcinogenic and toxic. However, in spite of the problems cited, there is no viable alternative to replace chromium, due to its exceptional technical characteristics, despite the growing interest in this subject in the last two decades. Thus, due to the increasing demands for materials and coatings with improved characteristics, especially in relation to corrosion resistance, the development of alternatives for the electrodeposition of hard chrome through unconventional baths, prepared from the addition of complexing agents to the electrolytes are currently an important area of research. These can form complexes with the metal ions of the electrolytes and can also be adsorbed onto the substrate surface, guiding the deposition and promoting homogeneous deposition rates in the areas of high and low current densities of the substrates. Thus, they have the ability to improve the quality and properties of the deposits compared to those obtained by conventional baths. One of the most widely used methods to evaluate the corrosion resistance of these coatings is linear potentiodynamic polarization (LPP). Through this technique, kinetic and thermodynamic parameters can be obtained that allow the evaluation of the corrosion resistance in different corrosive environments, and can provide information about the corrosion mechanisms. This work aims to obtain hard chrome deposits from non-conventional electrolytes and to evaluate their corrosion resistance in corrosive environments containing chlorides using the LPP technique.
Keywords: Cromo duro convencional; Agentes complexantes; Polarização potenciodinâmica linear; Corrosão; ENGENHARIAS::ENGENHARIA QUIMICA